Lipid metabolism in multiple myeloma: pathogenesis, therapeutic opportunities, and future directions - Wang, Huiquan; Zhang, Jiafeng; Ren, Hefei; Chen, Lei; Ren, Jigang; Liu, Chang; Wu, Hongkun; Zhou, Lin (Frontiers in Oncology, 2025)
Background: Multiple myeloma (MM) is a complex hematological malignancy characterized by the clonal expansion of plasma cells in the bone marrow. Emerging studies have emphasized the importance of lipid metabolism, which is closely associated with the survival, proliferation, and drug resistance of tumor cells. The hypoxic environment in the bone marrow (BM) contributes to metabolic reprogramming in MM cells, including alterations in metabolite levels, changes in metabolic enzyme activity, and metabolic shifts. Cancer cells possess the ability to adapt their metabolism in order to fulfill their continuously increasing energy demands. In this review, we will discuss the alterations in lipid metabolism during the development of MM, and their reciprocal interactions with the tumor microenvironment.